Against all enemies : inside america's war on terror - Clarke, Richard A. ([S.l.] : Free Press, 2004)
THE EXPLOSIVE INTERNATIONAL BESTSELLER With all-new excerpts from Richard Clarke's dramatic public testimony, and revealing corroboration from The 9/11 Commission Report From the 9/11 Commission Report: "On the day of the meeting [September 4, 2001], Clarke sent Rice an impassioned personal note. He criticized U.S. counterterrorism efforts past and present. The 'real question' before the principals, he wrote, was 'are we serious about dealing with the al Qida threat?...Is al Qida a big deal?... Decision makers should imagine themselves on a future day when the CSG has not succeeded in stopping al Qida attacks and hundreds of Americans lay dead in several countries, including the US,' Clarke wrote. 'What would those decision makers wish that they had done earlier? That future day could happen at any time.'"
Keywords: Qaida (Organization); September 11 Terrorist Attacks (2001); Terrorism--Government policy; United States; War on Terrorism (2001-2009)